Physical activity and health outcomes in persons with haemophilia B. (25th August 2014) - Niu, X.; Poon, J. L.; Riske, B.; Zhou, Z.Y.; Ullman, M.; Lou, M.; Baker, J.; Koerper, M.; Curtis, R.; Nichol, M. B.
Summary Regular participation in physical activity helps to prevent damage and maintain joint health in persons with haemophilia. This study describes self‐reported physical activity participation among a sample of people with haemophilia B in the US and measures its association with health‐related quality of life (HRQoL). Data on 135 participants aged 5–64 years were abstracted from Hemophilia Utilization Group Study Part Vb. The International Physical Activity Questionnaire assessed physical activity among participants aged 15–64 years, and the Children's Physical Activity Questionnaire abstracted from the Canadian Community Health Survey was used for participants aged 5–14 years. SF‐12 was used to measure HRQoL and the EuroQol (EQ‐5D‐3L) was used to measure health status for participants older than 18 years of age. PedsQL was used to measure HRQoL in children aged 5–18 years. Sixty‐two percent of participants in the 15–64 year‐old age cohort reported a high level of physical activity, 29% reported moderate activity and 9% reported low activity. For children aged 5–14 years, 79% reported participating in physical activity for at least 4 days over a typical week. Based on the 2008 Physical Activity Guidelines for Americans, 79% of adults achieved the recommended physical activity level. Multivariable regression models indicated that adults who engaged in a high level of physical activity reported EQ‐5D Visual Analogue Scale (VAS) scores that were 11.7 (P = 0.0726) points greater than those who engaged in moderate/low activity, indicating better health outcomes. Among children, no statistically significant differences in health outcomes were found between high and moderate or low activity groups.